Overexpression of BQ323636.1 Modulated AR/IL-8/CXCR1 Axis to Confer Tamoxifen Resistance in ER-Positive Breast Cancer - Tsoi, Ho; Shi, Ling; Leung, Man-Hong; Man, Ellen; So, Zi-Qing; Chan, Wing-Lok; Khoo, Ui-Soon (Life (Basel, Switzerland), 2022)
NCOR2 is a co-repressor for estrogen receptor (ER) and androgen receptor (AR). Our group previously identified a novel splice variant of NCOR2, BQ323636.1 (BQ), that mediates tamoxifen resistance via interference of NCOR2 repression on ER. Luciferase reporter assay showed BQ overexpression could enhance the transcriptional activity of androgen response element (ARE). We proposed that BQ employs both AR and ER to confer tamoxifen resistance. Through in silico analysis, we identified interleukin-8 (IL-8) as the sole ERE and ARE containing gene responsiveness to ER and AR activation. We confirmed that BQ overexpression enhanced the expression of IL-8 in ER+ve breast cancer cells, and AR inhibition reduced IL-8 expression in the BQ overexpressing cell lines, suggesting that AR was involved in the modulation of IL-8 expression by BQ. Moreover, we demonstrated that IL-8 could activate both AKT and ERK1/2 via CXCR1 to confer tamoxifen resistance. Targeting CXCR1/2 by a small inhibitor repertaxin reversed tamoxifen resistance of BQ overexpressing breast cancer cells in vitro and in vivo. In conclusion, BQ overexpression in ER+ve breast cancer can enhance IL-8 mediated signaling to modulate tamoxifen resistance. Targeting IL-8 signaling is a promising approach to overcome tamoxifen resistance in ER+ve breast cancer.